2019
DOI: 10.3389/fgene.2018.00688
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide SNP Data Revealed the Extent of Linkage Disequilibrium, Persistence of Phase and Effective Population Size in Purebred and Crossbred Buffalo Populations

Abstract: Linkage disequilibrium (LD) is a useful parameter for guiding the accuracy and power of both genome-wide association studies (GWAS) and genomic selection (GS) among different livestock species. The present study evaluated the extent of LD, persistence of phase and effective population size (Ne) for the purebred (Mediterranean buffalo; n = 411) and crossbred [Mediterranean × Jianghan × Nili-Ravi buffalo, n = 9; Murrah × Nili-Ravi × local (Xilin or Fuzhong) buffalo, n = 36] buffalo populations using the 90K Buff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 55 publications
(62 reference statements)
8
23
1
Order By: Relevance
“…The average distance over which LD decay dropped to the value of 0.2 was approximately 15 Kb for swamp and 50 Kb for river group, respectively. This finding was also supported by previous studies [5]. Moreover, it is well known that the Chinese indigenous breeds underwent a longer time of domestication compared with the river breeds.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The average distance over which LD decay dropped to the value of 0.2 was approximately 15 Kb for swamp and 50 Kb for river group, respectively. This finding was also supported by previous studies [5]. Moreover, it is well known that the Chinese indigenous breeds underwent a longer time of domestication compared with the river breeds.…”
Section: Discussionsupporting
confidence: 89%
“…Analysis of the genome-wide LD decay plays a vital role in the GWAS mapping of loci associated with economically important traits in livestock animals. Our previous studies have demonstrated that the LD extent was different between purebred and crossbred buffalo populations, with purebred having highest levels of LD [5]. In this study, we estimated the LD extent between river and swamp groups, showing that the LD decay in swamp group had declined markedly compared with the river group.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Historical relationships between populations were also identified, confirming two independent domestication events, one for river and one for swamp buffaloes. Deng et al (2019b) used the Affymetrix 90K SNP chip data from purebred river and crossbred river 9 swamp buffalo populations to evaluate the extent of LD, persistence of phase and effective population size, and suggested that performing these analyses should be routine as a preliminary step in advance of genomic selection and GWASs. Regarding the possible utilisation of the array outside the Asian water buffalo species, Iamartino et al (2017) found the 90K chip to be heavily affected by ascertainment bias.…”
Section: Snp Chipsmentioning
confidence: 99%
“…The presence of the extent of an effective population size (Ne), is an important population genetic parameter that has recently received a great deal of research attention [64], determining population demographic development [12] and demographic processes such as migration and admixture [45], and having profound implications for understanding the architecture of the animal genome [27,3]. In addition, Ne is widely regarded as one of the most critical population parameters because it measures the rates of genetic drift and inbreeding as well as affects the e cacy of systematic evolutionary forces such as mutation, selection, and migration [56].…”
mentioning
confidence: 99%